A Comprehensive Literature Review of Histopathology of Squamous Cell Carcinoma - Wahyu Agus Prastyo; Artha Investari Nugraheni (The Indonesian Journal of General Medicine, 2024)
Background: The literature on the histopathology of squamous cell carcinoma (SCC), particularly cutaneous squamous cell carcinoma (cSCC), has evolved significantly over the past decade, revealing a complex interplay of histopathologic features, molecular markers, and clinical outcomes.  Literature Review: The work by (K. El-Mofty, 2014) explores histopathologic risk factors associated with oral and oropharyngeal SCC variants, particularly those related to HPV. The identification of distinct morphological characteristics shared among keratinizing neoplasms is essential for accurate diagnosis and treatment planning. The article highlights the unique behaviors of HPV-related variants, which may exhibit either favorable prognoses or aggressive metastatic potential, thus necessitating careful evaluation. The role of immunohistochemical markers in the diagnosis and staging of cSCC is further elaborated by (Bălășescu et al., 2022), who identify key characteristics that predict disease progression. Their findings suggest that immunohistochemical markers can enhance diagnostic accuracy, particularly in poorly differentiated cases, thereby informing treatment strategies. Finally, (Gabriel Cocuz et al., 2022) provide a scientometric analysis of current research directions, highlighting the sustained interest in histopathology and immunohistochemistry of cSCC. Their work suggests an ongoing recognition of the importance of personalized diagnostics and targeted therapies to improve patient outcomes. Conclusion: In conclusion, the reviewed literature underscores the complexity of cSCC histopathology and the critical need for accurate diagnosis and staging. The integration of histopathological features with molecular markers and the continual evolution of diagnostic techniques are essential for refining our understanding of SCC behavior and enhancing treatment efficacy. Ongoing research is necessary to address existing challenges and optimize patient management strategies.